ANALISIS KESULITAN MAHARAH KITABAH DALAM PEMBELAJARAN BAHASA ARAB SISWA KELAS IX DI MTS MUHAMMADIYAH CIASMARA PAMIJAHAN BOGOR - Husna Ruhbiyat, Hasnul; Ahmad, Ahmad; Abdillah, Ubay (SHAWTUL ARAB, 2024)
This study was conducted in Mts 9th grade Muhammadiyah ciasmara pamijahan bogor.and this study is full of awareness of the importance of methods in the learning process. .and this study was conducted with the aim of knowing the students' ability to write Arabic both mufrodat or sentences. Rese Arabic because this became very important especially Arabic. One of the methods used is the qualitative descriptive method, i.e. displaying data on what happened to the student. this study was conducted to determine the students' Researchers therefore wanted to know the extent to which students could write. . What the researchers did was to use observation methods, interviews and tests on respondents who had been selected for the study. The results of the research in collecting data showed that out of tests and interviews from the population of 30 60% still could not write well. Difficulty in writing hijaiyah letters is 7, difficulty in writing sentences 9, difficulty in letter 8, difficulty in writing 6 so predominant in writing sentences and the conclusion of this study is that many still do not know in terms of sound, vocabulary, sentences and writing